NATIONAL IDENTITY AND THE WAYS OF ITS AFFIRMATION IN THE CONTEXT OF MULTICULTURALISM - Matyukhina, O. (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Introduction. The article outlines the key aspects of the development of the national communicative space in contemporary society. Within the context of the current global multicultural society, the formation and maintenance of a communicative space of national culture is a crucialcondition for preserving identity. The affirmation of national identity in the modern globalized world emerges as a response to the challenge of multiculturalism. The aim of the study is to conceptualize the communicative space of Ukrainian culture as a means of affirming national identity in both the social and personal dimensions. Research methods. To achieve the stated aim, the study employs a cultural-historical methodological approach, along with structural-functional, historical, and logical methods. Research results. The intensification of globalization and multiculturalism processes, in turn, stimulates the intensification of processes related to the affirmation of national identity. The article highlights new pathways for affirming national identity, such as festivals, modern communication technologies, and ethnodesign. These enrich the national dimension of the contemporary urban space and contribute to the affirmation of values, categories, and meanings of national culture within the social and individual communicative space. Emphasis is placed on the importance of dialogue with traditional culture and its creative appropriation for the optimal integration of Ukrainian society into globalization processes while preserving its own national identity. Discussion. The phenomenon of national identity and the ways of its realization in the context of multiculturalism are analyzed in the works of many domestic and foreign scholars. Conclusions. Multiculturalism in the modern world promotes not only cosmopolitanism and the spread of de-nationalized mass culture but also the activation of national self-identification processes. The affirmation and development of national identity are inherent to contemporary Ukrainian society. The foundation of this identity is Ukrainian culture. In the modern world, national communicative space serves as the basis for affirming national social and personal identity amidst the ongoing processes of globalization and multiculturalism.